Gamification by Design_ Implementing Game Mechanics in Web and Mobile Apps - Zichermann, Gabe (O’Reilly Media, 2011)
What do Foursquare, Zynga, Nike+, and Groupon have in common? These and many other brands use gamification to deliver a sticky, viral, and engaging experience to their customers. This book provides the design strategy and tactics you need to integrate game mechanics into any kind of consumer-facing website or mobile app. Learn how to use core game concepts, design patterns, and meaningful code samples to a create fun and captivating social environment.